COMBINING ABILITY FOR YIELD AND QUALITY TRAITS IN SINGLE CROSS HYBRIDS OF MAIZE (ZEA MAYS L.) - A. KRUPAKAR; KUMAR, BINOD; S. MARKER (The Bioscan, 2013)
Combining ability of some polygenic and quality traits was studied in a set of diallel crosses involving 10 maize inbreds (P1 to P10) to know the inheritance pattern of yield attributes. Analysis of variance exhibited highly significant differences among themselves for all the traits in all environments. The ratio of gca /sca was less than unity there by indicating the preponderance of non-additive gene effects in the expression of most of the characters studied. The parents P1 , P2 and P3 for grain yield, P5 and P8 for oil content, P6 , P8 and P9 for starch content and P7 , P8 and P10 for protein content were identified as most promising parents due to having good general combining ability. Among the crosses significant and desirable sca effects P3 × P1 and P3 × P2 for grain yield, P7 × P4 and P5 × P9 for oil content, P1 × P3 and P9 × P5 for starch content and P9 × P6 & P8 × P3 for protein content, respectively. Therefore, these crosses could be utilized for further selection of high yielding and quality progenies to achieve a quantum jump in maize improvement.